Postoperative pain: management and innovation - Nicola Maratea (Publiediting, 2022)
Despite the growing interest in the acute postoperative pain treatment and care, many steps need to be taken in both a technical and organizational sense to achieve optimal results. The most difficult problem to solve is the daily contrast between the clinical evidence of efficacy and the work differences in which every anesthetist finds himself operating. In our hospital, we have tried to reach a compromise between the adequate and updated use of technical and pharmacological resources and the organizational support of the individual healthcare realities. The basis of multimodal therapy is synergism, or mutual pharmacological enhancement, by associating sub-maximal doses of analgesic substances with different mechanisms of action to increase therapeutic power and reduce adverse effects.